Learning History Of Islamic Development In Indonesia And The Investment Of Local Values In Sma Negeri 1 Baturetno Wonogiri - Anang Harris Himawan (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
Education not only teaches understanding material, but also the formation of attitudes and media in preserving local culture. Planting local wisdom is important to apply because it is a means for students to better understand and love the culture they have. This study uses a qualitative method with a narrative approach. The informants in this study were history teachers and students of SMA Negeri 1 Baturetno. Observation data collection techniques, interviews and documentation. The data validity test used technical triangulation and source triangulation. Data analysis techniques with interaction analysis consisting of data collection, data reduction, data presentation, and conclusions. The results showed 1) planting local wisdom in the history of teaching teachers only developed their own learning related to regional culture. The planting of local wisdom tends to be in school activities outside of learning 2) the implementation of local wisdom values carried out by students has gone well. The values of local wisdom include ethics, aesthetics, religion, and social.